Improving the seismic performance of eccentrically braced frames by using a ductile element - Morteza Naghipour (Iranian Society of Structrual Engineering (ISSE), 2017)
Stability of structures against earthquake is much important to prevent total or partial failure of structures and loss of financial and human investments of people and country. Eccentrically braced frames, as one of the most commonly used earthquake resistant systems, with good ductility and toughness, have different arrangements; one of them is Link beam-to-column connection. This type of connection was considered as bending form before the North Ridge earthquake (1994). But conducted research after the North Ridge Earthquake showed that the link beam-to-column connections were subjected to brittle failure, similar to connections which were located in Moment frames. So, after the North Ridge Earthquake, researchers began looking for ways to improve these types of connections, which indicates necessity of research in this field more than before. In this study, a new type of Energy absorption was introduced.  This absorption consists of a ring which increases the ductility and energy absorption of earthquake and a box to increase the bearing capacity which is connected to the ring through connection plates. for evaluating the performance of the proposed elements in steel frames with eccentrically braces, under nonlinear time history analysis, the OpenSees software has been used. The obtained Hysteresis curves suggest that introduced element can act as an energy absorbing member and a fuse to Reducing damage to structures with reduced rotation of link-beam, Cutting base and Relative story displacement in addition to providing the necessary ductility.